Wilson’s disease: Food therapy out of trace elements - Li, Wen-Jie; Chen, Huan-Ling; Wang, Bin; Yao, Lei; Wang, Xiao-Ping (Frontiers in Cell and Developmental Biology, 2022)
Hepatolenticular degeneration, also known as Wilson’s disease (WD), is an autosomal recessive inheritance disorder of copper metabolism. The treatment of hepatolenticular degeneration emphasizes the combination of medical therapy and dietary therapy, such as a high zinc, low copper and sulfhydryl rich diet. Food therapy of WD based on trace elements is presented in this paper.